Drug Prevention and Control of Ventilator-Associated Pneumonia - Xie, Xinming; Lyu, Jun; Hussain, Tafseel; Li, Manxiang (Frontiers in Pharmacology, 2019)
Ventilator-associated pneumonia (VAP) is one of the most prevalent and serious complications of mechanical ventilation, which is considered a common nosocomial infection in critically ill patients. There are some great options for the prevention of VAP: i) minimize ventilator exposure; ii) intensive oral care; iii) aspiration of subglottic secretions; iv) maintain optimal positioning and encourage mobility; and v) prophylactic probiotics. Furthermore, clinical management of VAP depends on appropriate antimicrobial therapy, which need to be selected based on individual patient factors, such as previous antibacterial therapy, history of hospitalization or mechanical ventilation, and bacterial pathogens and antibiotic resistance patterns. In fact, antibiotic resistance has exponentially increased over the last decade, and the isolation of a multidrug-resistant (MDR) pathogen has been identified as an independent predictor of inadequate initial antibiotic therapy and which is significantly associated with increased mortality. Multiple attempts were used in the treatment of VAP, such as novel antibacterial agents, inhaled antibiotics and monoclonal antibodies. In this review, we summarize the current therapeutic options for the prevention and treatment of VAP, aiming to better manage of VAP in clinical practice.